2009
DOI: 10.26719/2009.15.1.219
|View full text |Cite
|
Sign up to set email alerts
|

Microbial contamination in the operating theatre: a study in a hospital in Baghdad

Abstract: Contamination of the operating theatre is a major cause of nosocomial infection. This study aimed to evaluate the incidence of bacterial contamination of operating theatres in Al Imam Ali Hospital in Baghdad, and the source of contamination. From 1216 swabs collected from surfaces, equipment and antiseptic solutions from different operating theatres in 2001 and 2002, the rates of positive cultures were 3.7% in 2001 and 4.0% in 2002. Staphylococcus epidermidis was the most common isolate in 2001 followed by Pse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
27
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 8 publications
13
27
4
Order By: Relevance
“…The prevalence (24.7%) of bacterial contamination revealed by this study is higher than a published study that was conducted in Iraq, where the authors found that in 1216 swabs, the percentage of samples that were positive for bacteria was 3.7% in 2001 and 4.0% in 2002 [2]; similar results were obtained in studies conducted in other countries [4,15,16]. However, the prevalence of bacterial contamination reported in this study is lower than the prevalence reported in a study conducted in Bangladesh (37.4%) [17].…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…The prevalence (24.7%) of bacterial contamination revealed by this study is higher than a published study that was conducted in Iraq, where the authors found that in 1216 swabs, the percentage of samples that were positive for bacteria was 3.7% in 2001 and 4.0% in 2002 [2]; similar results were obtained in studies conducted in other countries [4,15,16]. However, the prevalence of bacterial contamination reported in this study is lower than the prevalence reported in a study conducted in Bangladesh (37.4%) [17].…”
Section: Discussioncontrasting
confidence: 83%
“…Third, the study population was relatively small (243 samples). In a study similar to ours using only 91 samples, 37.4% of the samples were positive for contamination, whereas in a study using 1216 samples, only 4% of the samples were positive [2,17].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In these settings it is important to remember that the air flow into theatre is not the only potential source of contamination. Other important sources of infection are; poorly decontaminated equipment, the theatre built environment, theatre utilities [3] and inappropriate staff behavior [4]. Skin cells are constantly shed from theatre personnel.…”
Section: Introductionmentioning
confidence: 99%
“…Airborne microbial contamination of the indoor air environment of operating theatres (OT) is one of the risk factors for the development of post-surgical Infections (PSI) and had contributed to increased prevalence of nosocomial infections (NIs) (Al-Benna, 2012;Fleischer et al, 2005;Ensayel et al, 2009;Okon et al, 2012). About 10% of hospital acquired infections result in increased patient mortality, morbidity and length of hospital stay in addition to the overall costs of hospital admissions for post-operative surgery (Chacko et al, 2003;Reddy, 2012),Multiple sources have been previously reported as being associated with the contamination of the OT, including drainage of the wounds, ventilation systems, transportation of patients and collection bags, surgical team, degree of indoor traffic, theatre gown, foot wares, gloves, use of inadequately sterilized equipment and grossly contaminated surfaces (Okon et al, 2012;Fleischer et al, …”
Section: Introductionmentioning
confidence: 99%